Patterns of Ligature Marks in Hanging Versus Strangulation: A Comparative Autopsy Study - Ijaz Mehmood, Khurram Saleem, Ghulam Rasool, Gul Maria, Fozia Bibi, Nasim Irshad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Death due to hanging and strangulation is a critical medico-legal issue with significant forensic and public health implications. Differentiating these two types of deaths is essential for determining the cause, manner, and medico-legal consequences of death. Objectives: To compare the socio-demographic characteristics and medico-legal findings between deaths due to hanging and strangulation and to evaluate their associations with sex and type of death. Study Design & Setting: This retrospective study included 70 patients fulfilling inclusion criteria, with data collected from hospital records, medicolegal registers, and autopsy reports at Sheikh Zayed Medical College, Rahim Yar Khan (Jan 2021–Jan 2023), excluding incomplete records while maintaining confidentiality. Methodology: A total of 70 cases were included, consisting of 45 deaths due to hanging and 25 due to strangulation. Data regarding age, sex, ligature material, ligature mark site, and other relevant medico-legal parameters were collected. Statistical analysis was performed using the chi-square test to assess associations, with a p-value of <0.05 considered significant. Results: Most cases of hanging were reported in the 21–30 years age group (40.0%), while strangulation cases were more frequent in the 31–40 years group (36.0%). Hanging was predominant among males (62.2%), while strangulation had relatively higher female involvement (44.0%). The majority of cases in both categories involved rope as the ligature material. No statistically significant association was found between sex and type of death (p = 0.62). Conclusion: Hanging remains the most common cause of asphyxial death, particularly among young males, whereas strangulation is less frequent but relatively more common among females. Thorough medico-legal evaluation is crucial for accurate diagnosis. Keywords: Autopsy, Forensic medicine, Hanging, Medico-legal, Strangulation